Materials and Optimized Designs for Human‐Machine Interfaces Via Epidermal Electronics. (25th September 2013) - Jeong, Jae‐Woong; Yeo, Woon‐Hong; Akhtar, Aadeel; Norton, James J. S.; Kwack, Young‐Jin; Li, Shuo; Jung, Sung‐Young; Su, Yewang; Lee, Woosik; Xia, Jing; Cheng, Huanyu; Huang, Yonggang; et al.
<x xml:space="preserve">Abstract</x> Thin, soft, and elastic electronics with physical properties well matched to the epidermis can be conformally and robustly integrated with the skin. Materials and optimized designs for such devices are presented for surface electromyography (sEMG). The findings enable sEMG from wide ranging areas of the body. The measurements have quality sufficient for advanced forms of human‐machine interface. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>